Research on the Impact of ESG Performance on Cost of Corporate Debt Financing - Li, Entian; Yu, Jiabeizi (Transactions on Economics, Business and Management Research, 2024)
Over the past few years, green finance has emerged as a pivotal catalyst for the robust economic growth in China, achieving a level of standardization in its development. Concurrently, the ethos of responsible investment, anchored in Environmental, Social, and Governance (ESG) criteria, has increasingly captured the spotlight. This research leverages the CSMAR database to examine the A-share listed companies in China spanning 2009 to 2023, employing STATA16.0 for data analysis. The study's sample curation excludes ST/*ST firms, financial industry entities, and those with incomplete financial records. Additionally, the primary continuous variables were capped at the 1% and 99% quantiles to mitigate the impact of outliers, followed by descriptive statistics and correlation analysis, culminating in panel data regression model. The investigation zeroes in on the correlation between a company's ESG performance and the robustness of its corporate debt financing costs, with robustness tests adjusted for temporal considerations and alternative explanatory variables. The findings reveal a substantial negative correlation, suggesting that companies with superior ESG performance incur lower debt financing costs. This correlation is particularly pronounced among non-state-owned enterprises (non-SOEs). This underscores that in a fiercely competitive credit market, non-SOEs prioritize enhancing their brand value and market standing through ESG performance as a strategic move to bolster their intangible assets, thereby securing more favorable financing terms. Consequently, creditors should recognize the significance of a company's ESG performance, which is crucial for mitigating potential risks and ensuring the sustained and stable growth of businesses.